Aménagement forestier et participation : quelles leçons tirer des forêts communales du Cameroun ? - Mikaël Poissonnet; Guillaume Lescuyer (VertigO, 2005)
In addition to the forest management of large concessions and community forests of reduced sizes, communes of Cameroon launch out recently in the sustainable management of forests which are reassigned to them by the State. These Communal Forests represent an intermediate forest management between these two types of concessions. A plan of management is elaborate and a participative management must obligatorily be carried out in order to take account of the uses and interests of the local populations, which can vote against the mayor. The article seeks to determine whether this new model of management, contributing to increase the investment capacities of the commune and to the transfer of power of a central level towards a local level, may constitute a framework of a sustainable and participative management of the Central Africa tropical forest.